EVALUATION OF SHELF-LIFE OF FARM-RAISED CATFISH (Hemibagrus nemurus) FILLET STORED AT THE TEMPERATURE OF 5°C AND 10ºC - Hasan, Bustari; Leksono, Tjipto; ', Sakinah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was aimed to evaluate the shelf-life of farm-raised catfish (Hemibagrus nemurus) fillet stored at 5°C and 10ºC. Catfish, 250-350 gram in size was taken from cage aquaculture in Sungai Paku, Kampar. Thrity fish was sampled and filleted. The fillet were kept in plastic bag and stored in refrigerator at 5ºC and 10ºC for 15 days. Changes in quality during storage ware evaluated for sensory value, TVB (Total Volatile Base), TPC (Total Plate Count) and TBA (Thiobarbituric acid) and the evaluation was made at 0, 3, 6, 9, 12, and 15 day storage. Sensory quality of fish stored in 10±1⁰C incerased faster then that stored in 5ºC, and the fish was unacceptable after day-12 for fish stored at 5ºC and day-3 for fish stored at 10ºC. TVB and TBA value of fish stored at 10ºC increased faster than that stored at 5ºC. TPC value of fish stored at 10ºC also increased faster than that stored at 5ºC. The TVB, TBA and TPC value of fish stored at 10ºC was correlated stronger to sensory value than that stored at 5⁰C. TVB, TBA and TPC value of fish stored at 10°C and 5ºC at spoilage were 27.20 and 33.60 mg N/100; 0.15 and 0.19 mg malonaldehyde/kg; 5.33 and 6.11 log cfu/g respectively.Keywords: Catfish (Hemibagrus nemurus), shelf-life, temperature (5°C and 10ºC) and quality.